2017
DOI: 10.3389/fmicb.2017.02088
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Growth Promoters Modulate Broiler Gut Microbiome and Enhance Body Weight Gain

Abstract: Antibiotic growth promoters (AGPs) are frequently used to enhance weight-gain in poultry production. However, there has been increasing concern over the impact of AGP on the emergence of antibiotic resistance in zoonotic bacterial pathogens in the microbial community of the poultry gut. In this study, we adopted mass-spectrophotometric, phylogenetic, and shotgun-metagenomic approaches to evaluate bioactive phenolic extracts (BPE) from blueberry (Vaccinium corymbosum) and blackberry (Rubus fruticosus) pomaces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 45 publications
(59 reference statements)
7
61
1
2
Order By: Relevance
“…Bioactive compounds from berry pomaces and their extracts exhibited a wide range of biological activities, including antioxidant, anti-carcinogenic, anti-inflammatory, anti-neurodegenerative, and antiviral ( 12 , 13 ). These products showed concentration-dependent effects by modulating gut microbiota ( 14 , 15 ). Therefore, it is appropriate to explore these berry by-products as resources for different value-added applications.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds from berry pomaces and their extracts exhibited a wide range of biological activities, including antioxidant, anti-carcinogenic, anti-inflammatory, anti-neurodegenerative, and antiviral ( 12 , 13 ). These products showed concentration-dependent effects by modulating gut microbiota ( 14 , 15 ). Therefore, it is appropriate to explore these berry by-products as resources for different value-added applications.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the impact of nucleotides and Eimeria were independent on microbiota community but interactive on microbial activity. Instructively, there was a trend for decreasing alpha diversity with nucleotide supplementation commensurate to that seen with provision of antimicrobials (139). These changes on alpha diversity and in microbiota populations may have long-term impacts or may be further amplified with time.…”
Section: Utility Of Nucleotide Rich Yeast Extracts In Modulating Coccmentioning
confidence: 81%
“…The Firmicutes, however, constitute a heterogeneous phylum containing bacterial groups with different metabolic activities, which makes a change at the phylum level a less powerful indicator. Nevertheless, several studies on beneficial prebiotics in broilers have shown expansion of Firmicutes [ 32 ] or higher Firmicutes to Bacteroidetes ratios [ 52 ].…”
Section: Biomarkers Allowing Non-invasive Samplingmentioning
confidence: 99%